072 Understanding social and cultural influences on the relationships and sexual experiences of young British Pakistanis in London: is there unmet sexual health need?. (16th November 2010) - Griffiths, C; Prost, A; Hart, G J
Abstract : Background and aim: Health services should take account of cultural and faith diversity. Pakistanis are the UKs second largest ethnic group and one of the largest Muslim communities. However, relative to other ethnic minority groups, there is a paucity of sexual health research among this group. Using community-based qualitative research we explored the social and cultural influences on sexual attitudes and experiences of young Pakistanis in East London to determine whether there is unmet sexual health need and implications for service development. Design: Between June and September 2008, 30 in-depth one-to-one interviews (60–90 min) were conducted with young Pakistanis (n=22) and community workers working with Pakistani youth (n=8). Young Pakistanis were purposively selected across community settings: aged 16–25, born in UK and/or had been through UK secondary school. Interviews aimed to establish key life, social and cultural issues, with focus on relationship type and formation and perceived need/support. Interviews were recorded and transcribed verbatim. Analysis was thematic using "Framework" approach. Results: Many themes emerged which have a bearing on, and shape young Pakistanis' experiences of, relationships. Most experience parental restrictions on socialising and mixing with the opposite sex. For girls, behaviour is further monitored by older brothers and for both sexes "community policing" is an extension of this. However, young people have developed creative strategies to circumvent these restrictions and despite faith and cultural norms, relationships do take place, primarily in secrecy. This presents what are described as "conflicting pressures", "double worlds", and "multiple realities", which young people negotiate and move between, balancing different value systems. There were striking gender differences in perceptions and types of relationships and intimacy. For young women the ideal was a relationship for marriage. However, many described partners as "bad boys" and "gangster types" and some relationships were considered pressurised and "unhealthy". The young men made distinctions between girls deemed "wifey material" and those for casual relationships. Older boys (18+) were sexually active with partners from a range of ethnic backgrounds. Condom use was inconsistent. Though not sexually active, some of the other young people had experienced mutual touching and/or oral sex. Few had good sexual health knowledge and would not know where to access help. Conclusions: The secrecy within which young Pakistanis have relationships and the pressures and gender roles they negotiate mean that many may not receive the support they need. This has implications for the delivery of appropriate preventative and curative sexual health services.